Efeitos do exercício resistido e do laser de baixa potência na articulação talocrural em modelo experimental de artrite reumatoide - Retameiro, Ana Caroline Barbosa (2020)
Rheumatoid arthritis (RA) is an autoimmune disease that affects synovial joints and periarticular structures, especially those present in the limbs, causing pain and physical limitations for patients, which has an impact on life quality and reflects in socioeconomic issues, due to leave from work activities and treatment expenses. In an attempt to minimize its effects, therapeutic modalities have been used and, among then, physical exercise and low level laser therapy (LLLT). However, there are still gaps regarding the protocols used and the two therapeutic modalities association effects in the RA treatment. Thus, this study analyzed the resistance exercise and LLLT effects on ankle joint functional and morphological parameters in an RA model, promoted by complete Freund’s adjuvant (CFA). For this, 128 Wistar rats were used in the functional evaluations and 80 in the histomorphometric analyzes. The animals were submitted to the RA protocol acute and chronic phase of the disease 64 each for the functional ones and 40 each for the histomorphometry and each subdivided in control group (GC), arthritis group (GA), laser control (CL), exercise control (CE), laser control and exercise (CLE), laser arthritis (AL), exercise arthritis (AE), and laser arthritis and exercise (ALE), all with eight animals for functionality tests and five for histological analysis. In the arthritis groups, the induction occurred by applying CFA at the tail base, for immunization and, after, in the animals’ right tibiofemoral joint cavity. The treatments started 24 hours after the intra- articular injection, performed on alternated days with time and series progression for exercise. The grip, sciatic functional index (SFI) and inclined plane functional evaluations were performed on intra-articular injection day, 24 hours later and on 3rd and 5th days for acute group. For the chronic, the interval between evaluations increased to seven days, occurring on the 12th, 19th and 26th days. After the experimental period, the right ankle joints were processed and photodocumented for morphological and histomorphometric analyzes. All the analyzed parameters in the functional evaluations showed significant difference in the arthritis group in relation to the controls in two disease phases, with values returning similar to the control in the AL, AE and ALE groups, but with greater efficiency in the two treatments association. In the GA ankle joint morphology it was possible to observe angiogenesis in synovial membrane subintima and articular cartilage with pannus and flocculation, in both disease phases. The articular surface morphological changes were more expressive in chronic phase, since 50% of animals had such characteristics, and in acute only in some of them and with greater evidence in talus. In the acute phase, angiogenesis was also observed in the all other groups subintima, but with inflammatory infiltrate absence and with AE group being similar to the control in this aspect. In the same phase it was possible to notice a greater chondrocytes presence in GA, CE and AE, which was confirmed in the histomorphometric analysis which may indicate a more advanced tissue repair phase in these groups.